Characterization and climatic adaptation capacity of livestock farmers in two regions of Costa Rica - Cortés-Muñoz, Gerardo; Fuentes-Navarro, Eduardo; Mercado-Curi, Waldemar (Agronomía Mesoamericana, 2025)
Introduction. Dairy farms in Costa Rica have been classified into three different groups: specialized high-altitude dairies, specialized lowland dairies, and dual-purpose herds. However, this classification, does not consider the current production system diversity, where there is an important diversification in aspects such as sanitary, reproductive and feeding practices management. Objective. A dairy farms characterization in two representative livestock regions and their technology adoption capabilities to climate change was carried out. Materials and methods. To determine the technical-productive, social and economic characteristics of the Costarican dairy farms located in Chorotega and Huetar Norte Regions, a designed and validated survey was elaborated. The information was collected between April and May 2021, where 143 farmers were interviewed, allowing a total of 193 variables to be evaluated. Subsequently, the Cluster Analysis (CA) was performed by executing the hierarchical cluster analysis, using Ward's method. Results. Three clusters were integrated, thus determining high, medium and low farm management handling; and its relationship with ability to adapt to climate change. The first group was made up of farmers with superior r education level and farm management (high capacity), thus reflected in more adaptation strategies implemented. The farms of the second group (medium capacity), with less technical management, and the third farm group (low capacity), in which there were farmers with the lowest educational level, demonstrating a more limited technological management capacity. Conclusion. The livestock activity was characterized by three groups of producers with different capacities to adapt to climate change